Contribuições do design thinking para o desenvolvimento de competências dos profissionais do século XXI: revisão de literatura e pesquisa de campo - Cuque, Lucia Maria (2020)
The subject of this master’s dissertation is the use of design thinking in corporate environments. It involved a literature review and a field research. Its objective was to assess whether design thinking contributes to the development of the necessary competencies and skills for the 21st century professionals. This research understands design thinking as an approach that involves innovation and creative thinking to generate new ideas and explore alternative solutions for problem solving, including companies. In this sense, it is also a teaching and learning methodology aligned with constructivism which conceives learning as a social and interactive process and that can be used in corporate education. Bootcamp Bootleg, developed at Stanford University, defines five phases for the design thinking process: empathize, define, ideate, prototype and test. The research methodology was qualitative, field and exploratory. The literature review followed Okoli’s (2019) guidelines. Data collection was carried out through nine semi-structured interviews, which script was prepared considering the characteristics and processes of responsive interviews (Rubin & Rubin, 2011). Respondents are professionals who play or have played a role in design thinking sessions. Data analysis followed five coding criteria proposed by Saldaña (2013): versus coding, assessment coding, dramaturgical coding, provisional coding and hypothesis coding. The results showed that design thinking contributes to the development of personal and social professional competencies and skills, presenting results superior to those obtained with traditional teaching methodologies. The competencies and skills most frequently mentioned by the interviewees were: synthesis, collaboration, communication, cooperation, creativity, development of ideas, empathy, not giving up, open mind, patience and interpersonal relationship. The connection between the content and the teaching approach with the real and practical world proved to be fundamental for the professional learning and development. The research also showed that the fixed mindset of the professionals, the managers and / or the organizations can negatively interfere in the development of skills, unlike the growth mindset. The research concludes that design thinking can be successfully used in corporate education actions, if properly planned from the pedagogical perspective, to which this research contributed. This dissertation is inserted in the research line Learning and Cognitive Semiotics and in the research group GPTEd - Research Group in Educational Technologies